Characterization and validation of microsatelite markers for resistance to vascular streak dieback disease in cocoa (Theobroma cacao L.) - Waghmare Sandesh Tulshiram (Centre for Plant Biotechnolgy and Molecular Biology, College of Horticulture, 2016)
Cocoa is the third important plantation crop next to coffee and tea. The global production and consumption of cocoa is 27.00 lakh MT. Among the fungal diseases, Vascular Streak Dieback (VSD) caused by Ceratobasidium theobromae is the main constraint in cocoa growing countries, causing heavy losses in mature trees as well as seedlings. The VSD disease cannot be effectively controlled by chemicals and hence breeding for the development of resistant varieties is the best strategy to tackle the disease. In order to confirm the transfer of a desired gene into the offspring, conventional breeding methods rely on the field screening which will be highly influenced by the environmental factors. Marker assisted selection is an alternate where the tightly linked molecular markers will be employed to confirm the presence of the gene of interest in the selected plants. Five ISSR and one SSR markers linked to VSD resistance were identified at Kerala Agricultural University (Chandrakant, 2014). The present study was undertaken with the objective of validating the identified SSR and ISSR markers and to characterize the ISSR markers to identify the corresponding SSR markers. For validation and characterization, twenty VSD resistant hybrids and four susceptible clones were used. For molecular analyses, good quality genomic DNA was isolated from twenty four genotypes and ISSR markers UBC 811, UBC 815, UBC 826, UBC 857, UBC 866 and SSR marker mTcCIR 42 were screened. ISSR analysis had shown that all the primers are capable to differentiate resistant and susceptible genotypes. The SSR assay has also differentiated the resistant and susceptible genotypes. The distinct markers generated in resistant genotypes using UBC 811, UBC 826 and UBC 857 were eluted, cloned to pGEMT vector and sequenced. The nucleotide sequences were annotated using BLAST, ORF finder and SSR finder. The BLASTn of UBC811A and UBC811D nucleotide sequence have shown that this resistance locus lie in the chromosome V of Theobroma cacao genome. BLASTn of UBC826A, UBC826B and UBC857 has positioned these loci in chromosome III. ORF1 and ORF3 in UBC811D are shown to code for aflatoxin biosynthesis regulatory protein and NAD(P)H dehydrogenase quinine, respectively. ORF1 in UBC826B and ORF5 in UBC857-2 code for potassium transporter 27 (0sHAK-27) and structural polyprotein precursor of VP2, capsid protein VP2, respectively. All these proteins are identified to have definite roles in defence pathways. The frequency and distribution of SSR motifs, dimmers to decamers, in these ISSR markers and the corresponding primers were identified. The reported ISSR and SSR markers were validated and found to be successful in differentiating resistant and susceptible genotypes of cocoa; thereby these markers can be used in marker assisted breeding for VSD resistance.